Efficacy of vermicompost amended and bacterial diversity on plant growth and pathogen control - Raghda Zuhair; Abdel Naeim Al-Assiuty; Mohamed Khalil; Wesam Salama (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Organic solid wastes contain tremendous amounts of nutrients and beneficial microbes that cause environmental problems, such as pollution and shortage of dumping sites. Vermicomposting, considered as one of the most suitable stabilization and mass reduction methods, has been recognized for biowastes. This study aimed to evaluate the microbial diversity and analyze the ability of vermicompost produced from poultry litter, household, and guano of both insectivorous and frugivorous bats to reduce root-knot nematode's infection.Method The assessment of microbial diversity was carried out by amplification of 16s rRNA gene in bacteria habitant in vermicomposit . Nitrogen content, organic carbon constituent and heavy metal concentration were evaluated.Results The results obtained showed that organic matter ranged between 27.6% to 35.2%, while, C/N ratio was2.9 to 5.5 in the amended vermicomposite. Also,  there is a remarkable reduction in root-knot nematode infection after vermicopositing with organic wastes. Interstingly, the obtained bacterial species were Archangium gephyra, Corynebacterium glutamicum, Clostridium ultunense, Azospirillum sp. and Bacillus sp in biowastes.Conclusion According to these results, the produced vermicompost from different biodegradable wastes possesses bacterial diversity, lowers heavy metals' concentration, enhances plant growth parameter, and increases plant resistance against nematode infection.